Convertibles : an international perspective - Redmayne, Julian (London Euromoney Books, 1994)
The first part of the book looks at convertible instruments from three angles: an outline of the terminology used and some of the methods of examinng convertible value; the use of convetible instruments from an issuers' perspective; and finally convertible instruments from an investors' perspective. The second part of the book reviews the main domestic markets where convertible instruments exist. The markets examined in this part of the book are Japan, Switzerland, the United Kingdom and the United States. " The Chapters: Understanding Convertibles; Basic Conditions and Calculations; The Issuer's Perspective; The New Issue Process; The Secondary Market; The Investors' Perspective; The Euromarkets; Selected Domestic Convertible Markets. Jam-packed with graphs and tables.
lje 22/08/16
Loan
Keywords: International finance; Convertible securities; Foreign exchange